Labour mobility in the EU: addressing challenges and ensuring ‘fair mobility’ - Barslund, Mikkel; Busse, Matthias (Brussels, 2016)
"Labour mobility creates economic benefits for the EU at large and the mobile workforce. The same can be said for the special case of posted workers – a form of labour mobility that is crucial to the functioning of the internal market for services. Moreover, the number of posted workers is set to grow if the single market is further deepened. However, regulating the cross-border posting of workers – and ensuring a notion of ‘fair mobility’ – also epitomises the inherent difficulties in squaring the differences of 28 different sets of labour market regimes and regulations with the freedom to provide services in situ. In addition, the regulation has to work effectively in countries with large differences in income levels and social policies. This paper reviews the state of play with regard to posted workers and spell out the trade-offs involved to be kept in mind when considering the targeted revision of the posted workers Directive."